2021 European Conference on Optical Communication (ECOC) 2021
DOI: 10.1109/ecoc52684.2021.9606149
|View full text |Cite
|
Sign up to set email alerts
|

Real Time 100 Gbit/s/λ PAM-4 Experiments for Future Access Networks over 20 km with 29 dB Optical Budget

Abstract: We achieve 29 dB of optical budget and 20 km reach in a 50 Gbaud PAM-4 experiment at pre-FEC BER threshold of 10 -2 . A PDFA at OLT, a SOA-PIN at ONU are used in a real time experiment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…We study the impact of the optical amplifier location in three configurations: booster, preamplifier, and both booster and pre-amplifier targeting PtP and PtMP scenarios. The results are also compared with those obtained previously in [13] with a MZM Tx. The analog electrical finite impulse response (FIR) filter and its impact on the electrical modulation signal at the Tx-side are also presented.…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…We study the impact of the optical amplifier location in three configurations: booster, preamplifier, and both booster and pre-amplifier targeting PtP and PtMP scenarios. The results are also compared with those obtained previously in [13] with a MZM Tx. The analog electrical finite impulse response (FIR) filter and its impact on the electrical modulation signal at the Tx-side are also presented.…”
Section: Introductionmentioning
confidence: 79%
“…On the other hand, 100 Gbit/s with 4-level Pulse Amplitude Modulation (PAM-4) has been demonstrated with direct detection (DD) and offline DSP [9][10][11][12]. In [13], we showed that using a Mach-Zehnder Modulator (MZM) and DD, PAM-4 could be detected without DSP. Still, it is of further interest to assess if a DSP-free Rx could achieve high link budgets and properly detect a PAM-4 optical signal with a simpler transmitter (Tx) like an externally modulated laser (EML) composed of a monolithically integrated distributed feedback laser and an electro-absorption modulator.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is envisioned that a line rate at 100 Gb/s/λ will be required in future PON. Currently, PON with a line rate of 100 Gb/s/λ or more has been experimentally demonstrated based on the O-band intensity modulation and direct detection (IM/DD) scheme [4], [5]. The main problem of O-band IM/DD scheme is that the power budget margin and hence coverage reach is limited due to the higher optical power loss and accumulated chromatic dispersion at high symbol rate even within the O-band.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this problem, costly O-band booster (eg. praseodyme doped fibre amplifier [4] or Raman amplifier [5]) and pre-amplifiers are required at both optical line terminal (OLT) and optical network unit (ONU) sides, which increase the overall cost of PON system. With the widespread deployment of coherent optics in long-haul and metro transmission systems at C-band, coherent optics have now been introduced into the PON to provide longer Manuscript received December X, 2021.…”
Section: Introductionmentioning
confidence: 99%